Dietary intake and cardiovascular risk factors in Icelanders following a low carbohydrate diet - Aníta Sif Elídóttir 1990- (2015)
Background: Most available studies which have examined the effect of a low carbohydrate diet (LCD) on weight loss and risk factors for cardiovascular disease (CVD) are randomized controlled trails which place the main emphasis on total energy intake and macronutrient distribution rather than quality of the food consumed. The main aim of this thesis was to investigate dietary intake, food consumption and CVD risk factors among free living individuals who voluntarily follow a low carbohydrate diet. Methods: A cross-sectional study including 54 Icelandic individuals aged 20-66 years was conducted. All participants recorded their food intake for three consecutive days. Food data was entered into the food calculation program ICEFOOD, based on the Icelandic food database (ISGEM). Blood samples and anthropometric measurements were collected at the Landakot Hospital in Reykjavík. Results: More than two-thirds of the participants were women (70%). The mean of body fat percentages was 34 and 87% of participants were overweight, thereof 47% in the obese scale. The median intake of carbohydrate, protein, fat and saturated fat was 8%, 22%, 68% and 25% E respectively. As expected, consumption of fruits, bread, whole grain cereals, potatoes and pasta was very low, while consumption of meat and meat products was high, all compared to Icelandic mean intakes. The mean of blood glucose, serum total, LDL and HDL cholesterol, serum triglycerides and insulin were 5.3 mmol/l (range: 3.9 – 7.4 mmol/l), 5.2 mmol/l (range: 2.1-8.9 mmol/l), 3.1 mmol/l (range: 1.0 – 6.3 mmol/l), 1.6 mmol/l (range: 0.6 – 3.0 mmol/l), 0.9 mmol/l (range: 0.3 -2.1 mmol/l) and 7.6 mU/L (range: 1.1 – 22.6 mU/L), respectively. Conclusion: Our study shows that Icelandic individuals who voluntarily follow a LCD eat very low amounts of carbohydrates and very high amounts of total fat and saturated fatty acids (SAFA). As expected, dietary intake was thus in contradiction with dietary recommendations. Despite poor dietary intake and high prevalence of overweight and ...